Biaryl cross-coupling enabled by photo-induced electron transfer - Hayashi, Hirohito (2022)
We report a protocol for aryl cross-coupling of electron-deficient aryl halides with electron-rich (hetero)arenes that is driven solely by violet light. This process takes advantage of formation of photo-excited state of electron-deficient aryl halides, that are reduced by electron-rich (hetero)arenes to form a pair of aryl anion and cation radicals. The resulting aryl anion radicals of aryl halides undergo mesolysis of the carbon-halogen bond to generate aryl radicals, that are coupled most likely with aryl cation radicals to afford functionalized biaryls. (Figure presented.).